Entrepreneurship from the perspective of small business support entities - António Oscar Santos Góes; Talles Vianna Brugni (Tourism & Management Studies)
In this paper we discuss the entrepreneurship phenomena from the perspective of five supporting entrepreneurial organisations in the city of Itabuna – Bahia, Brazil. The entrepreneurial environment, strategies and challenges encountered in the opening, continuity and succession of business formed the theoretical scope. We examined the modus operandi of entrepreneurs in the management of micro and small firms. The research used a qualitative approach, both exploratory and bibliographic. The fieldwork was based on interviews and content analysis systematised the information collected. The interview results revealed strengths and weaknesses in the local business environment. The results show a business setting with contradictory situations: on the one hand, full of opportunities while on the other hand there are many uncertainties to overcome. Most entrepreneurs develop actions/strategies empirically, and experience is the most common factor in business administration.